NEUROD polymorphism Ala45Thr is associated with Type 1 diabetes mellitus in Czech children - Cinek, Ondrej; Drevínek, Pavel; Sumník, Zdenĕk; Bendlová, Bĕla; Sedláková, Pavlína; Kolousková, Stanislava; Snajderová, Marta; Vavrinec, Jan (Diabetes research and clinical practice, 2003)
Association of the NEUROD Ala45Thr polymorphism with Type 1 diabetes mellitus (DM) has been found in some but not all populations. We performed a study on the association of two NEUROD exon 2 polymorphisms, the Ala45Thr and the Pro197His, with childhood-onset Type 1 DM in the Czech population. We compared 285 children with Type 1 DM diagnosed under the age of 15 years with 289 non-diabetic control children. The genotypes were determined using novel real-time allele-specific PCR assays in the TaqMan format, and data were analysed using logistic regression. The numbers of subjects with codon 45 genotypes Ala/Ala, Ala/Thr, Thr/Thr were 95, 145, 45 among cases and 117, 130, 42 among controls. Thr45 phenotypic positivity was associated with a significant risk of Type 1 DM (OR=2.01, CI 95% 1.25-3.24) in a multivariate logistic regression model involving also the insulin gene -23HphI genotype and the presence of Type 1 DM-associated HLA-DQB1*0302-DQA1*03 (DQ8) and DQB1*0201-DQA1*05 (DQ2) molecules. No association was observed for the Pro197His mutation which was carried by 5.3% cases and 5.9% controls. Our results confirm that the NEUROD Ala45Thr polymorphism is associated with childhood-onset Type 1 DM.
Keywords: threonin; Threonine; proteiny nervové tkáně; Humans; sekvence nukleotidů; DNA primery; Mutation, Missense; Nerve Tissue Proteins; dítě; Child; frekvence genu; lidé; mladiství; Regression Analysis; diabetes mellitus 1. typu; missense mutace; Base Sequence; Insulin; Alanine; HLA-DQ Antigens; Adolescent; motiv helix-loop-helix; alanin; polymerázová řetězová reakce; HLA-DQ antigeny; Czech Republic; DNA Primers; Polymerase Chain Reaction; Gene Frequency; transkripční faktory bHLH; Helix-Loop-Helix Motifs; věk při počátku nemoci; Česká republika; Age of Onset; regresní analýza; Diabetes Mellitus, Type 1; inzulin; Basic Helix-Loop-Helix Transcription Factors